Exploring the Wisdom of Da'wah: Character Building Akhlaq al-Karīmah Santri Pesantren Al Kahfi Bangkalan, Indonesia - Alvin Khoiron (An-Nur International Journal of Islamic Thought, 2023)
This research aims to investigate the critical role of Pondok Pesantren Al Kahfi (PP Al Kahfi) in shaping the character of akhlaq al-karīmah students. Moral character, which includes commendable traits such as kindness, patience, sincerity, and integrity, is highly valued in Islam. This research method involves collecting data through interviews with leadership staff, boarding school administrators, and students. Field observations were conducted to gain a deeper understanding of the character-building process of akhlaq al-karīmah in this boarding school. The results showed that Pondok Pesantren Al Kahfi School has a variety of educational and da'wah programs designed to shape students' character by the principles of akhlaq al-karīmah. The teachers and administrators of the boarding school play an important role in providing good examples and educating students about the importance of akhlaq al-karīmah in daily life. This study concludes that Pondok Pesantren Al Kahfi has successfully carried out its role in shaping the character of students who are akhlaq al-karīmah through real education provided by boarding school administrators. These results can be the basis for a better understanding of how Pondok Pesantren plays a role in forming good character among students